Respuesta :

Answer: 6 and 8

Step-by-step explanation: Call the first number x and the second number y.

One number is two less than the second number so x=y-2 (*)

Twice the second number is 2 less than 3 times the first gives us,

2y=3x-2

Substituting equation (*) into this equation gives,

2y=3(y-2)-2 which solves to give y=8 and (*) gives x=6

The two numbers should be 6 & 8 respectively.

Given that

  • The one number is 2 that less than the second number.
  • Also, it is twice the second number is 2 that less than 3 times the first.
  • Let us assume the one number be x and the other number be y.

Based on the above information, the equations are as follows:

x = y - 2    ...........(i)

2y = 3x - 2............(ii)

Now put the value of x in equation (ii)

2y = 3(y - 2) - 2

2y = 3y - 6 - 2

2y - 3y = -6 -2

-y = -8

y = 8

So, x should be

= 8 - 2

= 6

Therefore, we can conclude that the first and other number be 6 and 8 respectively.

Learn more: brainly.com/question/17429689

ACCESS MORE